2017
DOI: 10.1021/acsami.7b12104
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Graphene–Polyimide Nanocomposites with Superior Electrical Conductivity

Abstract: We report on the fabrication of a novel class of lightweight materials, polyimide-graphene nanocomposites (0.01-5 vol %), with tunable electrical conductivity. The graphene-polyimide nanocomposites exhibit an ultra-low graphene percolation threshold of 0.03 vol % and maximum dc conductivity of 0.94 S/cm, which we attribute to excellent dispersion, extraordinary electron transport in the well-dispersed graphene, high number density of graphene nanosheets, and the π-π interactions between the aromatic moieties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 59 publications
1
47
0
Order By: Relevance
“…Meng et al have shown the use of an interconnected PI‐supported 3D graphene structure as a basis for flexible electrodes for lithium‐ion batteries. Recently, Yoonessi et al produced a graphene–PI nanocomposite containing well‐dispersed graphene nanosheets. The maximum conductivity achieved was 0.96 S cm −1 at a filler content of 5 vol%.…”
Section: Polyimide–carbon Nanocompositesmentioning
confidence: 99%
See 4 more Smart Citations
“…Meng et al have shown the use of an interconnected PI‐supported 3D graphene structure as a basis for flexible electrodes for lithium‐ion batteries. Recently, Yoonessi et al produced a graphene–PI nanocomposite containing well‐dispersed graphene nanosheets. The maximum conductivity achieved was 0.96 S cm −1 at a filler content of 5 vol%.…”
Section: Polyimide–carbon Nanocompositesmentioning
confidence: 99%
“…Figure c shows a scanning tunneling microscopy (STM) image at atomic resolution of the 3D‐C with a hexagonal symmetry modulation of 0.246 nm periodicity . Figure d shows an SEM image depicting the interconnected macroporous structure of the 3D‐C/PI electrode produced by Meng et al Figure e shows a low‐magnification transmission electron microscope (TEM) image revealing the dispersion of the graphene layers and stacks in the nanocomposite produced by Yoonessi et al, with graphene concentration of 1.23 vol%. Both high particle number density of the graphene layers and stacks were evident.…”
Section: Polyimide–carbon Nanocompositesmentioning
confidence: 99%
See 3 more Smart Citations